Assessment of microbial quality in poultry drinking water on farms in Austria - Mustedanagic, Azra; Matt, Monika; Weyermair, Karin; Schrattenecker, Anna; Kubitza, Isabella; Firth, Clair L.; Loncaric, Igor; Wagner, Martin; Stessl, Beatrix (Frontiers in Veterinary Science, 2023)
The quality of poultry drinking water has a significant effect on broiler health and performance. This study conducted an analysis of aerobic mesophilic counts (AMC), Enterobacteriaceae (EB), Pseudomonadaceae (PS), and screened for the presence of Campylobacter spp. in water samples collected from a total of 14 farms in Austria, with either a public or private water source. The efficacy of two water line treatment methods was evaluated: a chemical treatment of the water lines with 4.0 ppm ClO2 (T1) and a combined chemical (4.0 ppm active ClO2 and 3.0% peracetic acid) and mechanical treatment (purging of the water lines with a high-pressure air pump; T2). However, both the T1 and T2 treatments failed to reduce the AMC counts below the maximum acceptable microbial limit of 4.0 log10 CFU/ml in water samples. In addition, no significant reduction in EB and PS counts was observed in water samples after either T1 or T2 water line treatment. The water samples showed a high level of microbial diversity with 18 to 26 different genera. The genus Pseudomonas was most frequently isolated across all poultry farms, while C. jejuni was identified in a single sample collected before water line treatment. Isolate analysis revealed the presence of opportunistic pathogens in water samples both before (T1 43.1%, T2 30.9%) and after (T1 36.3%, T2 33.3%) water line treatment. Opportunistic pathogens belonging to genera including Pseudomonas spp., Stenotrophomonas spp., and Ochrobactrum spp., were most frequently isolated from poultry drinking water. These isolates exhibited multi-drug resistance and resistance phenotypes to antimicrobials commonly used in Austrian poultry farms. The findings of this study emphasize the potential risk of exposure to opportunistic pathogens for poultry and personnel, underscoring the importance of efficient water line management.